Meningkatkan Hasil Belajar Siswa Dengan Menggunakan Model Pembelajaran Project Based Learning Pada Mata Pelajaran IPA Materi Sumber Energi Kelas IV Di SDN 3 Mataram Tahun Pelajaran 2023/2024 - Ari Inayatur Rahmatillah; Musahadah Musahadah; Moh.Irawan Zein (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
This study was designed to improve student learning outcomes in science using a project-based learning model for students of class IV SDN 3 Mataram. Based on the observation of the fourth grade teacher of SDN Negeri 3 Mataram on Tuesday, March 28, 2023, namely Ibu Ayu, it is known from the interview that SDN 3 Mataram is a primary school that is still actively implementing the 2013 curriculum. participation in the lesson because the teaching model used by teachers usually only involves the teacher speaking and the teacher does not use different teaching models. This study uses qualitative descriptive data analysis, where this study correctly describes the reality, which is facilitated by data collection methods and analysis of relevant data obtained from scientific situations. According to the results of training cycles 1 and 2 after using the PjBL teaching model, it can be seen that in the initial conditions, the percentage of completion of studying scientific material on Energy Resources was only 43.7%, but at the same time, the increase in the completeness of student learning after using the PJBL training model in cycles I and cycle II respectively - 62.5% and 78.1%, respectively. Student completion increased by approximately 15.6%.